THE SOUTH BORDER: THE YCHMA ARCHEOLOGY VIEW FROM THE VALLEY OF MALA - Tantaleán, Henry (2008)
In this paper we show a serial of jerarchized approachs that we expect help to define and to delimit concret and conceptually the real, methodological and epistemological borders of the society knowed in the archaeological literature as Ychma, which one was settled specificly in the Lurin and Rimac valleys at the central peruvian coast during the prehispanic period called Late Intermediate (circa 900 DNE- 1470 DNE) but survived in many socioeconomic and sociopolitical aspects to the Inca occupation of the area. To carry out such approachs we have based in our knowledge of the social materiality described as Ychma y, above all, in it dialectical negation in the south part of the central coast recognized for us in the area of the Mala river valley, where we have almost a decade of fieldwork and understanding of the social phenomenae both intra and inter valley.